Retracted: Evaluation of factors influencing drug adherence to anti retroviral therapy (ART) in a tertiary care hospital, Guntur Andhra Pradesh, India - Mattam, Bheemesh Naidu; Akurathi, Mounika; Krishna, B.M.S.G; Tumati, Haritha Reddy (International Journal of Basic & Clinical Pharmacology, 2017)
The article "Evaluation of factors influencing drug adherence to anti retroviral therapy (ART) in a tertiary care hospital, Guntur Andhra Pradesh, India" is retracted by the Editor and Publisher, as per the request of corresponding author Dr. Bheemesh Naidu Mattam and co-authors, due to an unintended mistake. The Moriskys Medication Adherence Scale (MMAS-8) was used without proper permission.